Differences in the cytological features of atypical adenomatous hyperplasia and low-grade prostatic adenocarcinoma - (:unkn) unknown (My University, 2010)
Amaç: Bu çalışmada, atipik adenomatöz hiperplazi'nin histolojik özelliklerinin gözden geçirilmesi ve prostatik adenokarsinom Gleason grade 1 ve 2'den ayırt edebilecek parametrelerin ortaya konması amaçlanmıştır. Sitolojik özellikleri ile ilişkili 14 parametre incelenmiştir. Gereç ve Yöntem: Yüz beş radikal prostatektomi materyalinde 11 atipik adenomatöz hiperplazi (22 odak) ve 15 prostatik adenokarsinom Gleason grade 1 ve 2 (22 odak) tespit edilmiştir. Bazal hücrelere özgü keratin (34βE12) uygulanmış ve prostatik adenokarsinom Gleason grade 1 ve 2 lezyonların bazal hücre içermemesi esas alınarak lezyonlar atipik adenomatöz hiperplazi ve prostatik adenokarsinom Gleason grade 1 ve 2 olarak gruplandırılmıştır. Bulgular: İki lezyon arasında, en büyük nükleus çap ortalaması nükleus yerleşimi, 1-2 μm nükleol, >2 μm nükleol, multipl nükleollu nükleus özellikleri bakımından istatistiksel olarak anlamlı fark bulunmuştur. İncelenen diğer parametreler olan nükleer membran düzensizliği, nükleus çap ortalaması, kromatin paterni, piknotik nükleus, nükleer pleomorfizm, <1 μm nükleol, nükleoler marginasyon (nükleer membrana değen nükleol varlığı), sekretuar hücre nükleus/ sitoplazma oranı, sekretuar hücre sitoplazmik görünümü her iki lezyonda benzer özellik göstermiştir. Sonuç: Çalışmamızda, histomorfolojik özelliklerin birlikte değerlendirilmesinin, atipik adenomatöz hiperplazi ve prostatik adenokarsinom Gleason grade 1 ve 2 lezyonların ayırıcı tanısında önemli olduğu sonucuna varılmıştır.

Objective: The aim of this study was to review the histological features and to define parameters distinguishing atypical adenomatous hyperplasia from prostatic adenocarcinoma grade 1 and 2. We evaluated 14 parameters related with cytological properties. Material and Method: We found 11 atypical adenomatous hyperplasia (22 foci) and 15 prostatic adenocarcinoma grade 1 and 2 (22 foci) lesions in 105 radical prostatectomy specimens. Basal cell-specific keratin (34βE12) was applied and based on the fact that prostatic adenocarcinoma grade 1 and 2 lesions do not have basal cells we grouped the lesions as atypical adenomatous hyperplasia and prostatic adenocarcinoma grade 1 and 2. Results: Statistically significant differences were found between atypical adenomatous hyperplasia and prostatic adenocarcinoma grade 1 and 2 lesions for some parameters including the largest nuclear diameter, nuclear location, 1-2 μm nucleolus, > 2 μm nucleolus, and nuclei containing multiple nucleoli. We found similar properties between the two lesions for the following parameters: irregularity of nuclear membrane, median diameter of the nucleolus, chromatin pattern, pynotic nucleus, nuclear pleomorphism, < 1 μm nucleolus nucleolar margination, and the ratio of nucleus to cytoplasm and the appearance of cytoplasm in the secretory cells. Conclusion: Evaluation of the overall histomorphological criteria is important in the differentiation of atypical adenomatous hyperplasia and prostatic adenocarcinoma grade 1 and 2 lesions.
Atipik adenomatöz hiperplazi ve düşük dereceli prostatik adenokarsinomların sitolojik özelliklerindeki farklılıklar
Keywords: Cerrahi